The cabin in the woods [videorecording (Blu-Ray)] - Goddard, Drew, 1975-; Whedon, Joss, 1964-; Hemsworth, Chris; Connolly, Kristen, 1980-; Hutchison, Anna, 1986-; Kranz, Fran, 1983-; Williams, Jesse, 1981-; Acker, Amy, 1976-; Julyan, David; Deming, Peter (Lions Gate Home Entertainment, 2012)
A rambunctious group of five college friends steal away for a weekend of debauchery in an isolated country cabin, only to be attacked by horrific supernatural creatures in a night of endless terror and bloodshed. As the teens begin to exhibit standard horror movie behavior, a group of technicians in a control room are scrutinizing and sometimes even controlling every move the terrified kids make. Do they have any chance of escape?